Nonerosive reflux disease :comparative analysis of symptoms severity, endoscopic and 24-hours ph-impedance - Nordin, Noorlina (2015)

(untitled)
Background : Non--‐erosive reflux disease (NERD) has emerged as a real entity in the spectrum of gastroesophageal reflux disease (GERD) and may, indeed, represent the most common manifestation of reflux disease. NERD is defined as presence of troublesome reflux symptoms and the absence of mucosal breaks at endoscopy.There are many studies done regarding NERD, but none of the study looks into the symptom severity , endoscopic and 24--‐hours pH--‐ impedance monitoring. Our aim is to compare the symptom score with endoscopic and pH--‐ impedance monitoring with the endoscopic findings. Methodology : This was a prospective study of patients presenting with various upper gastrointestinal symptoms between 1st June until 30th November 2014. From all, patients with nonerosive reflux disease were included after the upper endocopy ( excluding erosive reflux disease) and multiple esophageal biopsies were taken from multiple level of oesophagus. From all the NERD patients, 24--‐hours ambulatory pH--‐impedance monitoring will be done in all consented patients. Results : From this study, we conclude that the severity score for dysphagia (p value 0.003), the possibility for esophageal changes observed from upper gastrointestinal endoscopy were expected. A total of 28 NERD participants underwent 24--‐hour pH studies. The median (IQR) DeMeester score was 4.94 (11.90) but none of the endoscopic findings were expected in positive pH study in NERD population. We also found 3 patients with eosinophilic esophagitis with prevalence of 3.6%. Conclusion : The study showed a significant association between symptom score for dysphagia, with positive endoscopic (esophagitis ) findings , and there were no association between endoscopic changes in positive pH study in NERD population.